Urusei yatsura. 3 - Takahashi, Rumiko, 1957-; Nieh, Camellia (Viz signature., 2019)
"Beautiful space alien princess Lum invades Earth in her UFO, and unlucky Ataru Moroboshi's world gets turned upside down! What unimaginable shenanigans will Lum bring to Ataru's life? One thing's for sure: nearly every moment is electrifying with her around! Undeterred by Lum's jealous anger, Ataru continues to shamelessly chase skirts. When the priestess Sakura returns as Tomobiki High School's nurse, the school is plagued by unprecedented menaces that titillate Ataru's lecherous heart! Later, Lum's gorgeous childhood friend Ran escalates the school hijinks, but what Lum doesn't know is that Ran has a major score to settle!"--